Analysis of Caesarean Section Rates in a Tertiary Care Hospital through Robson's Ten Group Classification System (RTGCS) - Akhtar, Rubina; Shams, Ghazala; Iqbal, Madiha; Ahmed, Basharat; Jan, Zara Alam; Nawaz, Aisha (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Objective To analyse the trend of caesarean sections at a tertiary care hospital according to Robson’s Ten Group Classification System Methodology This retrospective study was conducted at the department of obstetrics and gynecology Unit “B” Hayatabad Medical Complex, Peshawar from January to December 2019. Data for all births including live births and stillbirths by C-section (n=1538) was extracted from the patient’s record and grouped into Robson’s 10 categories. Data was analyzed using descriptive statistics and the outcome expressed as frequencies and percentages. Results During the study period, 5609 women were delivered in this hospital. The overall cesarean section was 27.42%. The leading contributor to the overall cesarean section rate was group 5 i.e. women with previous cesarean section, the contribution being 6.63% of the overall 27.42%. Conclusion The Robson classification is an effective tool to identify the areas/factors which significantly contribute to the high C-section rate and accordingly provide basis to formulate strategies aimed to decrease the C-section rate. Key words Caesarean section, Robson’s Ten Group Classification System